2014
DOI: 10.2174/1874285801408010015
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Efficacy Testing of a Bioelectric Wound Dressing Against Clinical Wound Pathogens

Abstract: Silver-based wound dressings have been developed for the control of bioburden in wounds. However, the popularity and extensive use of silver-based dressings has been associated with emerging microbial resistances to silver. In this study we examined in vitro antibacterial efficacy of a bioelectric dressing containing silver and zinc against various wound pathogens. Antibiotic-sensitive clinical wound isolates showed a 100% reduction in bacterial growth, except that Enterococcus faecalis isolate was shown to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…A recent device, a redox-active Ag/Zn bioelectric dressing, increases keratinocyte migration to facilitate wound closure, needs no external power source, conforms to skin topography and can be cut to the size of the wound (Banerjee et al, 2014 ). Similar wireless bioelectric dressings generate a micro-electrical field which may augment the natural electric field of injury following wounding (Kim et al, 2014 ), and have bactericidal activity on numerous wound pathogens including multidrug resistant organisms (Kim et al, 2016 ). In another study in chronic wounds unresponsive to conventional therapies, a bioelectrical signal therapy device generating an AC pulse train with a stochastic (random) signal led to 87% of the wounds undergoing closure (Fraccalvieri et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent device, a redox-active Ag/Zn bioelectric dressing, increases keratinocyte migration to facilitate wound closure, needs no external power source, conforms to skin topography and can be cut to the size of the wound (Banerjee et al, 2014 ). Similar wireless bioelectric dressings generate a micro-electrical field which may augment the natural electric field of injury following wounding (Kim et al, 2014 ), and have bactericidal activity on numerous wound pathogens including multidrug resistant organisms (Kim et al, 2016 ). In another study in chronic wounds unresponsive to conventional therapies, a bioelectrical signal therapy device generating an AC pulse train with a stochastic (random) signal led to 87% of the wounds undergoing closure (Fraccalvieri et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many texts refer to bacterial bio-burden greater than 10 5 CFU/mL organisms per gram of tissue as a criterion for infection [3,6]. In this study we used 2×10 5 In previous studies [13,14,15], it has been demonstrated that the concentrations required to kill S. aureus is higher than P. aeruginosa which is time dependent. DLF required higher concentrations to kill the bacteria that are beyond those clinically achievable with antibiotics, implying that DLF on its own could not effectively inhibit P. aeruginosa based infections.…”
Section: Discussionmentioning
confidence: 99%
“…Persistent infection impairs wound healing causing repeating inflammatory cycle, resulting in chronic wounds [3,4]. Prevention and control of infection have been identified as essential aspects of wound management [5]. Effective management requires reducing exogenous microbial contamination, debridement, using appropriate dressing(s) and administration of topical and systemic broad-spectrum antimicrobial agents [6].…”
Section: Introductionmentioning
confidence: 99%
“… 13 In in vitro testing, the MCD was observed to exhibit an electricidal effect in the presence of antibiotic and multidrug resistant clinical wound isolates. 14 MCD demonstrated greater bactericidal activity versus silver and controls in in vitro testing, and effectively killed bacteria tested on in vitro biofilm models. 15 , 16 In in vivo porcine studies, evidence of reduced early wound inflammation was observed along with increased epithelial thickness.…”
Section: Introductionmentioning
confidence: 98%